Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/polym14122445
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Shielding Effectiveness of Woven Fabric with Integrated Conductive Threads after Washing with Liquid and Powder Detergents

Abstract: The paper investigates the shielding effectiveness of a newly developed cotton and polyester fabric into which conductive stainless-steel threads were incorporated in the warp and weft directions at frequencies 0.9 GHz, 1.8 GHz, 2.1 GHz, and 2.4 GHz. As resistance to external influences and degradation is an additional critical factor for protective textiles, the newly developed protective fabric was exposed to cumulative wash cycles with liquid and powder detergents, which were targeted to preserve the shield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…Other current researches related to EMS fabrics mainly focus on the numerical model calculation (Liu and Wang, 2020), structural characteristics (Yin et al, 2022), performance improvement (Zhang et al, 2021;Pusic et al, 2022), influencing factors analysis (Wang et al, 2021;Toghchi et al, 2020), test evaluation (Vohra and El-Shenawee, 2021), new product Carbon nanotube fiber's effect development (Uzun et al, 2021;Tunakova et al, 2020) and new mechanism research (Yang et al, 2021;Kumar et al, 2021). However, these efforts have not addressed the simultaneous improvement of EMS and wave absorbing properties in EMS fabrics, nor have they explored the application of carbon nanotubes in EMS fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…Other current researches related to EMS fabrics mainly focus on the numerical model calculation (Liu and Wang, 2020), structural characteristics (Yin et al, 2022), performance improvement (Zhang et al, 2021;Pusic et al, 2022), influencing factors analysis (Wang et al, 2021;Toghchi et al, 2020), test evaluation (Vohra and El-Shenawee, 2021), new product Carbon nanotube fiber's effect development (Uzun et al, 2021;Tunakova et al, 2020) and new mechanism research (Yang et al, 2021;Kumar et al, 2021). However, these efforts have not addressed the simultaneous improvement of EMS and wave absorbing properties in EMS fabrics, nor have they explored the application of carbon nanotubes in EMS fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research found that cyclic washing of electromagnetic shielding fabric (EMS)—polyester/cotton fabric with integrated stainless steel threads (PES/CO/SS)—with specifically formulated powder and liquid detergent had an effect on the loss of protective characteristics. If the electromagnetic shield effect (EMSE) is monitored at higher frequencies, the composition of the powder and liquid detergents is appropriate [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shielding properties of the fabric were measured before and after professional care processes, including dry cleaning and wet cleaning in two variations at frequencies of 0.9 GHz, 1.8 GHz, 2.1 GHz, and 2.4 GHz. The influence of process parameters of dry and wet cleaning on the mechanical damage of the fabric was additionally analyzed using microscopic examination of the surface [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the research of this aspect is still slow, and the existing mainly focuses on the numerical model calculation [ 4 ], structural characteristics [ 5 ], performance improvement [ 6 , 7 ], influencing factors analysis [ 8 , 9 ], test evaluation [ 10 ], new product development [ 11 , 12 ], and new mechanism research [ 13 , 14 ]. At present, improving the SE of the EMS fabric and retaining the inherent porous characteristics lack effective methods.…”
Section: Introductionmentioning
confidence: 99%